The Antihelminthic Activities of Dita (Altonia scholaris) Bark and Tamarind (Tamarindus indicus) Seeds: A Comparative Study - Florentino, Carmela M.; Supnet, Gemma Agnes R. (JPAIR Multidisciplinary Research, 2010)
The study was done to compare the antihelminthic activities of dita (Alsonia scholaris) bark and tamarind (Tamarindus indicus) seeds using adult earthworms, Pheretima posthuma. It was found out that the dita bark extract showed more potent antihelminthic activity as compared to the tamarind seeds. Further, the antihelminthic activity of the two plant extracts were also compared to the antihelminthic activity of a known standard drug, mebendazole Results showed that the dita bark extract has stronger antihelminthic action against the worm than mebendazole.
Keywords: Antihelminthic activity; Dita (Alstonia scholaris) bark; Tamarind (Tamarindus indicus ) seeds; Mebendazole; Earthworm; Paralysis time; Death Time